The Strengthening Government Policies on Mineral and Coal Mining to Achieve Environmental Sustainability in Indonesia, Africa and Germany - Akhmaddhian, Suwari; Budiman, Haris; Bhandari, Rahul (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Indonesia has enacted a number of regulations dealing with issues of mining governance, and governance. However, the issuance of these various laws and regulations has resulted in illegal mining crimes resulting in environmental damage. The purpose of this study is to analyze sustainable mining governance policies in Indonesia, Africa and Germany. This research method uses a doctrinal legal approach. Resources have been compiled through an examination of mineral and coal mining laws and regulations, governance and environmental governance regulations, as well as reports from various authorities on the same subject. The results of this study show how Indonesia's previous mining law policies recognized local governments as the authority for licensing and monitoring mining activities. This policy was revoked based on the latest governance regulations and had an impact on the vacancy in monitoring mining activities at the district/city level, as a result of this vacancy there was environmental damage due to illegal mining and bad mining activities so that it was necessary to strengthen government policies in monitoring mineral and coal mining. Mining governance policies in Indonesia, Africa and Germany are currently starting to lead to environmental sustainability.